Comparison and modelling of extraction methods to assess agronomic effectiveness of fertilizer zinc. Issue 2 (14th February 2020) - Degryse, Fien; da Silva, Rodrigo C.; Baird, Roslyn; Cakmak, Ismail; Yazici, Mustafa Atilla; McLaughlin, Mike J.
Abstract: Total Zn in fertilizer is a poor predictor of Zn availability in granular fertilizers. In this study, we compared different extraction methods using Zn fertilizers for which the agronomic effectiveness had previously been determined. Sixteen fertilizers were extracted by eight different procedures using five extractant solutions: water, 1 M ammonium acetate (pH 7.0), 74 mM EDTA (pH 7.0), 5 mM DTPA + 0.1 M MES (pH 6.2), and 0.12 M bis‐tris (pH 6). Modelling of Zn solubility and speciation was carried out with a chemical speciation program (Visual Minteq). The predicted solubilities were in good agreement with the observations, indicating chemical equilibrium. The three methods using pure water were highly correlated with each other and showed the strongest correlation with agronomic effectiveness ( r = 0.81–0.90). The methods using extractants with strong pH buffering or high chelating capacity showed no or weak correlation with the agronomic effectiveness. Thus, water‐only based methods give the best indication of the availability of Zn in granular fertilizers, and are best suited for regulation or labeling of available Zn in fertilizer.